Chicken or egg? What comes first in Lutheranism, grace or faith?: A brief refresher course on Lutheran soteriology. Issue 2 (9th March 2021) - Tarkki, Jarmo
Abstract: For many Lutherans Martin Luther's idea of salvation by grace alone is complicated and confusing. Acceptance of salvation as God's work alone seems scandalous. We want our efforts to matter to God, and so we become inadvertently God's co‐workers in our own salvation. Modern humans tend to fall into the same trap from which Luther liberated himself. In a Lutheran interpretation of Christianity, we are not saved because we have faith, but we have faith because we are saved. In the article, the interplay between grace and faith is addressed throughout history with main emphasis on a Lutheran understanding of saved by grace alone.